A SURVEY REGARDING THE AWARENESS OF THERMOPLASTIC RESINS AMONG BULGARIAN DENTISTS AND DENTAL TECHNICIANS - Bozhana Chuchulska; Stoyan Yankov; Ilian Hristov; Diyan Slavchev; Lyubomir Grozev (Peytchinski Publishing, 2018)
Thermoplastic materials (TMs) are used more than a century in dentistry worldwide, but in Bulgaria, there is limited information about their properties and indications. These materials let the specialists widen the application of full and partial dentures even in difficult clinical cases. Objective: A survey regarding the awareness of the properties, the drawbacks and the indications of the thermoplastic materials for dental purposes in Bulgaria. Material and method: Inquiry ranged from April 2016 until October 2016. The participants were 289 dentist and dental technicians in Bulgaria. The questions regard area of expertise, gender, age, years of experience; awareness of the types of TMs, members and working protocol; properties of the materials, personal observations of the participants. Results: Most of the participants work in a private practice, and half of them are familiar with the TMs in general. Conclusion: This study shows that 52% of the participants are aware of have some information about TM, 82% of them know the polyamides, 25% the thermoplastic acrylic resins, 15% polyoxymethylene, 4% polyolefin and only 1,5% Polyan. 42% use these materials in their practice and are familiar with the technological and working protocol and only 36% report that they are aware of their properties, disadvantages and indications.